Radiation dose tracking in computed tomography: Red alerts and feedback. Implementing a radiation dose alert system in CT. Issue 1 (February 2021) - Crowley, C.; Ekpo, E.U.; Carey, B.W.; Joyce, S.; Kennedy, C.; Grey, T.; Duffy, B.; Kavanagh, R.; James, K.; Moloney, F.; Normoyle, B.; Moore, N.; et al.
Abstract: Introduction: This study investigates instances of elevated radiation dose on a radiation tracking system to determine their aetiologies. It aimed to investigate the impact of radiographer feedback on these alerts. Methods: Over two six-month periods 11, 298 CT examinations were assessed using DoseWatch. Red alerts (dose length products twice the median) were identified and two independent reviewers established whether alerts were true (unjustifiable) or false (justifiable). During the second time period radiographers used a feedback tool to state the cause of the alert. A Chi–Square test was used to assess whether red alert incidence decreased following the implementation of radiographer feedback. Results: There were 206 and 357 alerts during the first and second time periods, respectively. These occurred commonly with CT pulmonary angiography, brain, and body examinations. Procedural documentation errors and patient size accounted for 57% and 43% of false alerts, respectively. Radiographer feedback was provided for 17% of studies; this was not associated with a significant change in the number of alerts, but the number of true alerts declined (from 7 to 3) (χ2 = 4.14; p = 0.04). Conclusion: Procedural documentation errors as well as patient-related factors are associated with false alerts in DoseWatch. Implementation of a radiographer feedback tool reduced true alerts. Implications for practice: The implementation of a radiographer feedback tool reduced the rate of true dose alerts. Low uptake with dose alert systems is an issue; the workflow needs to be considered to address this.